Functional neuroimaging in obesity and the potential for development of novel treatments. Issue 8 (August 2016) - Schlögl, Haiko; Horstmann, Annette; Villringer, Arno; Stumvoll, Michael
Summary: Recently, exciting progress has been made in understanding the role of the CNS in controlling eating behaviour and in the development of overeating. Regions and networks of the human brain involved in eating behaviour and appetite control have been identified with neuroimaging techniques such as functional MRI, PET, electroencephalography, and magnetoencephalography. Hormones that regulate our drive to eat (eg, leptin, insulin, and glucagon-like peptide-1) can affect brain function. Defects in central hunger signalling are present in many pathologies. On the basis of an understanding of brain mechanisms that lead to overeating, powerful neuroimaging protocols could be a future clinical approach to allow individually tailored treatment options for patients with obesity. The aim of our Review is to provide an overview of neuroimaging approaches for obesity (ie, neuroimaging study design, questions which can be answered by neuroimaging, and limitations of neuroimaging techniques), examine current models of central nervous processes regulating eating behaviour, summarise and review important neuroimaging studies investigating therapeutic approaches to treat obesity or to control eating behaviour, and to provide a perspective on how neuroimaging might lead to new therapeutic approaches to obesity.